Reliability and validity of a taekwondo electronic body protector - Razman, R.; Chong, R. W. L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2019)
The Protector and Scoring System was introduced in taekwondo to encourage transparency in scoring during competition. The system, which has been used in the past two Olympics, consists of two main components, the electronic body protector and socks. The few studies that have been conducted on the Protector and Scoring System have not been comprehensive and used questionable testing methods. The main objectives of this study were to methodologically examine the validity and reliability of a Protector and Scoring System body protector. To fulfil these objectives, a customized mechanical pendulum was built to test the Protector and Scoring System. The reliability of the pendulum was first determined by tracking the pendulum`s mean velocity at impact for 50 trials on two separate occasions. Data from both days were compared and showed no significant differences (p = 0.08). Mean kinetic energy of the pendulum was then calculated to be 55.52 J. For the experimental trial, the electronic body protector was divided into 12 sections. Each section was tested with the pendulum for 50 trials on two separate days. It was found that only three sections had no significant differences between the two days (p > 0.01), while the rest of the sections had significantly different readings between Day 1 and Day 2. Based on the homologous descriptive statistics, only two sections were in the same group, which translated to the Protector and Scoring System being only 16.7% reliable overall for both days. In terms of validity, an independent samples t-test was used to determine the differences between the calculated kinetic energy from the pendulum (the criterion) and the displayed kinetic energy on the Protector and Scoring System, and values were found to be significantly different (p < 0.01). Overall, the reliability and validity of the Protector and Scoring System was found to be questionable. The system needs to be examined exhaustively before being used in any future tournaments.